The Policy Model of Development for Educational Management in Education Sandbox Areas in Thailand - Khuandeja, Thanoo; Sirisunhirun, Somboon (Journal of Posthumanism, 2025)
This research aimed to analyze factors influencing educational management in education sandbox areas using confirmatory factor analysis (CFA), and to develop an educational management model. This study employed a mixed research methodology, involving both quantitative and qualitative methods with a total of 1,892 participants by random sampling method in Education Sandbox Areas. The study samples included members of the Policy Committee, the Provincial Education Sandbox Innovation Areas Committee, administrators, teachers, students, and parents, selected through purposive sampling. Data were collected using questionnaires and semi-structured interviews. The model indices included Chi-square statistical values, Index (GFI), Index (AGFI), Index (CFI), Index (NFI), Index (NNFI), and (RMSEA). The findings highlight six key components: personnel development, environmental management, budgeting, administration, learning management, and participatory networks. Effective educational leaders require a comprehensive understanding of educational management frameworks within innovative education settings. Furthermore, personnel and environmental development emphasize continuous professional development for teachers to adapt to respond to the societal demands. Educational institutions benefit from the strategic utilization of locally available resources to develop teaching and learning materials in alignment with their operational capacity. This approach facilitates the efficient allocation of resources and promotes cost-effective budget management within the educational sector.